Hijabers Community: Upaya Muslimah Urban Indonesia dalam Membentuk Feminine Space - Putri Aisyiyah (Jurnal Spektrum Komunikasi, 2019)
This paper focuses on the phenomenon of urban society that tends not to give place to women, especially Muslim women wearing veils. This condition leads to the efforts of a group of Moslem women to create their own space, known as the concept of feminine space. Advances in information technology and communications make this movement gains momentum. Through virtual media, namely Facebook and Twitter, this movement proceeds to create a community of women with hijabs (Hijabers Community). HC community has a mission to change the public perspective that the hijab represents traditionality into a different view that women with hijabs are modern, fashionable, and dynamic. This work aimed to reveal that HC is more than a virtual community, it is a movement as these women attempt to get space in urban society. The writer interviews the initiators of Hijabers Community, to find out how they describe themselves, how they perceive the surrounding environment, and how they view the relationship between them and other groups in urban society.